2016
DOI: 10.1111/boer.12071
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Transition Towards the Renminbi's Full Convertibility: Implications for China's Growth

Abstract: There is a widespread consensus that China needs to rebalance its export-driven growth paradigm towards a more consumption-based one and that such process is to be accompanied by the transition towards the renminbi's full convertibility. However, the Chinese authorities have so far acted with great caution because this transition cannot but accelerate the slowdown of China's growth which will likely occur because of other structural factors. We address these issues by means of a twocountry two-stage (before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…On this aspect, empirical studies by Bahmani-Oskooee and Gelan (2013) on African countries also reported mixed results. Although Bonatti and Fracasso (2016) cautioned that by lifting the capital control and free float of Renminbi will restrict the Chinese authorities’ ability of market intervention and resource allocation, one cannot dispute that the choice of the exchange rate regime is purely a sovereign nation’s internal affair. In principle, the point of argument could be the issues around competitive devaluation due to the beggar-thy-neighbour consequences.…”
Section: Introductionmentioning
confidence: 99%
“…On this aspect, empirical studies by Bahmani-Oskooee and Gelan (2013) on African countries also reported mixed results. Although Bonatti and Fracasso (2016) cautioned that by lifting the capital control and free float of Renminbi will restrict the Chinese authorities’ ability of market intervention and resource allocation, one cannot dispute that the choice of the exchange rate regime is purely a sovereign nation’s internal affair. In principle, the point of argument could be the issues around competitive devaluation due to the beggar-thy-neighbour consequences.…”
Section: Introductionmentioning
confidence: 99%